Gender Differences in the Empathy–Recidivism Relationship - Narvey, Chelsey S. (Criminal justice and behavior, 2023)
A large body of criminological research often focuses on risk factors that propel individuals toward criminal activity rather than those that act as protective factors to reduce criminal involvement. In this study, we focus on a potentially important protective factor, empathy, which has long been considered an individual characteristic related to prosocial human behavior including non-offending. Specifically, we test the effects of empathy on juvenile recidivism and evaluate how empathy interacts with gender as a protective factor among a large sample of adjudicated youth followed for 1-year post-release from a residential treatment facility. Results show that empathy was associated with lower recidivism among the entire sample of youth, with a stronger protective effect against recidivism for justice-involved female youth. Findings contribute to the gendered literature on responses to crime and suggest empathy should be included in programming and interventions for youth involved in the juvenile justice system, particularly for females.